PROVIDING LANDSLIDE DISASTER MITIGATION EDUCATION TOWARDSIMPROVING KNOWLEDGE AND ATTITUDES OF CITIZENS IN DISASTERRESPONSE SITUATIONS - Yeni Nur Rahmayanti; Eka Novitayanti; Fadma Aji P; Christiana Ari P; Pipi Anonyma (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Landslides are the movement of soil or rock masses from slopes, generally triggered by heavy rain, earthquakes, or human activity. This condition indicates the importance of serious attention to disaster risk reduction efforts to minimize impacts and increase community resilience. Lack of information from residents regarding disaster mitigation and disaster response attitudes that have not been fostered. Providing education to improve residents' knowledge and disaster response attitudes. This study aims to analyze the effect of Landslide Disaster Mitigation Education on the Level of Knowledge and Attitudes of Residents in Disaster Response Situations. The method used is quantitative with a quasi-experimental design. Using total sampling, with a population of Jenawi villagers with a sample of 55 respondents. Data analysis used the Wilcoxon Test. The results of the Wilcoxon Test showed a p-value of 0.001 or a p-value of ˂ 0.05. This indicates that there is an effect of Landslide Disaster Mitigation Education on the Level of Knowledge and Attitudes of Residents in Disaster Response Situations. It can be concluded that providing education through the lecture method can increase knowledge about disaster mitigation and disaster response attitudes.